DEVOSI PAGI DALAM PENDIDIKAN AGAMA KRISTEN SEBAGAI SARANA PEMBENTUKAN KARAKTER DI SDS DIAN HARAPAN DAAN MOGOT JAKARTA - Ester Rahayu; Timotius Sukarna (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
Christian Religious Education, also known as Pendidikan Agama Kristen or PAK is a way of teaching that helps students grow in all areas of life. The government wants schools to help students become mature in their spirit, morals and minds. Christian Religious Education plays a role in this by helping students develop spiritually in a school setting. This study looks at how well morning devotion activities help students develop character. We live in a time where many people are losing values, so this is very important. The study found that when students take part in morning devotion activities, they do not just learn about values they start to live with. This happens when these activities are done in a sustainable way. The study also found that the way morning devotion is done is very important. It needs to be managed in a way that makes sense for each school. It needs to be structured and reflective. When homeroom teachers are heavily involved and mentor their students closely it makes a difference. They act as guides for their students. So, morning devotion is not something that students have to do every day. It is a time for them to learn and live out Christian values in their daily lives. Christian Religious Education and morning devotion activities are important, for internalizing Christian values into students' daily behaviours.